2016
DOI: 10.1111/1440-1681.12582
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enoxaparin on seroma and mesh‐tissue adhesion in a hernia model

Abstract: The aim of this study was to investigate whether enoxaparin (ENX) administration would increase seroma risk and worsen mesh tissue recovery in an experimental rat hernia repair model. Fifty-six adult male Wistar-Albino rats were included in the study. Rats were equally and randomly separated into seven groups: Group 1, Control, only subcutaneous dissection was performed; group 2, Sham, Hernia defect was primary sutured; Group 3, Prolene mesh; Group 4, Dual mesh; Group 5, ENX + Sham; Group 6, ENX + Prolene mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These guidelines are absent in animals. A study in rats (LOE 6, Fair) demonstrated increased seroma formation and reduced healing at the site of a mesh hernia repair if rats received enoxaparin therapy during surgery . From a procedural standpoint, intrapleural heparin therapy was associated with increased survival in dogs with pyothorax (LOE 5, Poor) …”
Section: Pico Question: Discontinuation Of Heparins Before Surgerymentioning
confidence: 99%
“…These guidelines are absent in animals. A study in rats (LOE 6, Fair) demonstrated increased seroma formation and reduced healing at the site of a mesh hernia repair if rats received enoxaparin therapy during surgery . From a procedural standpoint, intrapleural heparin therapy was associated with increased survival in dogs with pyothorax (LOE 5, Poor) …”
Section: Pico Question: Discontinuation Of Heparins Before Surgerymentioning
confidence: 99%